Statistical explanation of the protective effect of four COVID-19 vaccine doses in the general population - Reyes, Humberto; Méndez, Constanza; Kalergis, Alexis M. (Frontiers in Public Health, 2023)
Objectives: To assess the effectiveness of four doses of the vaccine against SARS-CoV-2 in the general population and the impact of this on the severity of the disease by age group. Methods: By using data from the health authority public data base, we build statistical models using R and the GAMLSS library to explain the behavior of new SARS-CoV-2 infections, active COVID-19 cases, ICU bed requirement total and by age group, and deaths at the national level.The four doses of vaccine and at least the interaction between the first and second doses were important explanatory factors for the protective effect against COVID-19. The R 2 for new cases per day was 0.5644 and for occupied ICU beds the R 2 is 0.9487. For occupied ICU beds for > 70 years R 2 is 0.9195 and with the interaction between 4 doses as the main factor.Although the increase in the number of vaccine doses did not adequately explain the decrease in the number of COVID-19 cases, it explained the decrease in ICU admissions and deaths nationwide and by age group.The pandemic caused by SARS-CoV-2 between 2020 and 2022 has caused a major public health burden with large number of deaths worldwide (1). As of 23 May 2023, a total of